2017
DOI: 10.1002/ghg.1723
|View full text |Cite
|
Sign up to set email alerts
|

Impact of salinity on CO2containment security in highly heterogeneous reservoirs

Abstract: It is well established that brine salinity can vary substantially in prospective CO2 geo‐storage reservoirs. However, the impact of salinity on containment security has received only little attention. We thus used a compositional reservoir simulation to evaluate the effect of salinity on CO2 plume migration and CO2 trapping capacities in a 3D heterogeneous reservoir. The used heterogeneous reservoir consists of two formations: the bottom part of the reservoir is a fluvial reservoir, and the top part represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 105 publications
5
27
0
Order By: Relevance
“…The corrosion of quartz increases as the time increases at high temperature and pressure. 14 In sum, carbonate minerals such as calcite and Na-feldspar dissolve during CO 2 flooding. Such dissolution increases the porosity of the inlet part of the core sample, which leads to the migration of the cementation and silicate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The corrosion of quartz increases as the time increases at high temperature and pressure. 14 In sum, carbonate minerals such as calcite and Na-feldspar dissolve during CO 2 flooding. Such dissolution increases the porosity of the inlet part of the core sample, which leads to the migration of the cementation and silicate.…”
Section: Discussionmentioning
confidence: 99%
“…Between the solution system and minerals of the target core, dissolution interactions are as follows 26, 27 : CaC normalO3+normalH+Cnormala2++ HCO 3 trueleft2 NaAlS i3O8+2H++9H2normalOleft1emnormalAl2normalSi2O5 OH 4+2normalNa++4H4 Si O4 trueleft CaA l2normalSi2O8+2H++H2normalOleft1emnormalAl2normalSi2O5 OH 4+normalCa2++2H4 Si O4 Si normalO2+2normalH2OnormalH4 Si normalO4During the flooding, water–rock interactions are mainly the dissolution of calcite and Na‐feldspar. The corrosion of quartz increases as the time increases at high temperature and pressure . In the literature, batch experiments conducted by Mandalaparty at high temperature and high pressure were also observed to result in the precipitation of calcite and kaolinite of sandstone samples in the presence of CO 2 .…”
Section: Co2–water–rock Interaction Experimentsmentioning
confidence: 91%
See 2 more Smart Citations
“…The effectiveness of the trapping mechanisms depends on various geological and hydraulic parameters, including geological reservoir heterogeneities, caprock properties, CO 2 ‐rock wettability, reservoir temperature, wettability heterogeneity, and brine salinity . Moreover, although many geological parameters cannot be changed for a particular site, it has been shown that intelligent selection of CO 2 injection technology (e.g.…”
Section: Introductionmentioning
confidence: 99%